The animal presence in «Muro noroeste» and «Los caynas» by César Vallejo - Luján Sandoval, Sergio (2023)
The aim of this work is to demonstrate that the presence of the animal, in two stories of Escalas (1923) by César Vallejo —«Muro noroeste» and «Los caynas»—, is a tremor against anthropocentric precepts and against Western rationality. For this, we will make a brief exhibition on what we understand as a vanguard of ideas. Then, we will review the coordinates of anthropocentrism and reason, and how in the avantgardes these dogmas begin to be questioned. Finally, we will analyze the stories «Muro noroeste» and «Los caynas»; for this, respectively, we will dialogue with the guidelines offered by the biopolitics related to the notions of bios and zoé, as well as what is understood, in a widespread way, as animality. Thus, it is possible to argue that, in the Peruvian vanguard, the animal breaks the metaphorical-allegorical perimeter to emerge as a space saboteur and divergent from the hegemonic, and fruitfully ambiguous.